THE INFLUENCE OF MASS MEDIA ON HUMAN PSYCHOLOGY - Usmonov Sherzod Axmadjonovich; Nishonov Islomjon Ilhomjon o‘g‘li (Journals Park Publishing, 2022)
The mass media is the most important, powerful and effective tool of ideology, and the fact that information attacks are frequently organized recently indicates that the attitude towards war has changed and a new type of weapon has been discovered. This weapon is information. It is about targeting the mind and heart of a person in information wars conducted with the help of such a weapon, the use of the Internet, the sudden appearance of Internet sites used by terrorists in the world today, information attacks and ways to combat them.
Keywords: television, computer, internet, mobile phone, information, terrorist organizations, mass media, telegram.